A nonlinear control scheme based on dynamic evolution path theory for improved dynamic performance of boost PFC converter working on nonlinear features. (November 2016) - Mohanty, Pratap Ranjan; Panda, Anup Kumar
Abstract: This paper is concerned to performance improvement of boost PFC converter under large random load fluctuation, ensuring unity power factor (UPF) at source end and regulated voltage at load side. To obtain such performance, a nonlinear controller based on dynamic evolution path theory is designed and its robustness is examined under both heavy and light loading condition. In this paper, %THD and zero-cross-over dead-zone of input current is significantly reduced. Also, very less response time of input current and output voltage to that of load and reference variation is remarked. A simulation model of proposed system is designed and it is realized using dSPACE 1104 signal processor for a 390 V DC, 500 W prototype. The relevant experimental and simulation waveforms are presented. Abstract : Highlights: Real time validation of DEC controlled boost PFC system by dSPACE 1104 processor. Enhanced converter performances under load and reference variation. The dead-zone at cross-over of source current during light load is eliminated. Proposed controller governs the system dynamic ensuring zero steady-state error. Inherent features: UPF, limited %THD, sinusoidal source current, regulated output.